2021
DOI: 10.3390/ijerph18168830
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the COVID-19 Pandemic on Total Hip and Knee Arthroplasty Surgical Volume in 2020 in Poland

Abstract: The aim of this study was to analyse the effect of the first year of the COVID-19 pandemic on total hip arthroplasty (THA) and total knee arthroplasty (TKA) surgical volume in Poland. A retrospective analysis of data concerning THA and TKA collected by the National Health Fund in Poland in 2019 and in 2020 has been conducted. The number of primary hip or knee arthroplasties in 2020 was around 71% and 67% of the number registered in 2019, respectively. There was also a decline in the volume of revision arthropl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 32 publications
(40 reference statements)
2
10
0
4
Order By: Relevance
“…Current total joint arthroplasty studies evaluating the decline in case volume due to COVID-19 are limited by lack of sample size and annual trend analysis. The few studies on this topic are either from countries outside the United States, review articles, single institutional evaluations, small multicenter collaborations, or simple projections based on historical data [4,[14][15][16][17][18][19]. Lowry Barnes et al analyzed Medicare Claims limited to the first quarter of 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Current total joint arthroplasty studies evaluating the decline in case volume due to COVID-19 are limited by lack of sample size and annual trend analysis. The few studies on this topic are either from countries outside the United States, review articles, single institutional evaluations, small multicenter collaborations, or simple projections based on historical data [4,[14][15][16][17][18][19]. Lowry Barnes et al analyzed Medicare Claims limited to the first quarter of 2020.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] As a result, there has been a decrease in the number of elective surgeries, including joint prosthesis implantation. [ 11 ] Thus, our challenge is to address the needs of patients who require such surgeries. There have been detrimental changes in health in patients who have postponed elective procedures during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Similar conditions have also been seen in surgeries ( 6 ). The impact of the pandemic on surgical volume may lead to postponement of elective surgeries ( 7 9 ), which may have unfavorable effects on patient outcomes ( 10 ). In fact, a recent global survey ( 11 ) showed that hip fracture service was disrupted during the pandemic, thereby impacting health and social care experienced by the patients.…”
Section: Introductionmentioning
confidence: 99%